(untitled) (Texas Journal of Medical Science, 2024)
This article presents a literary review of the anatomy of the pelvic region and its clinical significance in medicine and surgery. The authors emphasize the complexity and importance of studying the anatomy of the pelvic region, especially in the context of minimally invasive surgery and intraoperative procedures. Vascular structures, including the sacral venous plexus and arterial vessels, their role in blood supply to organs and tissues are analyzed. The need to develop minimally invasive methods to stop intraphase bleeding is highlighted. The relevance of further research aimed at understanding the interaction of balloon devices with vascular and nervous structures is indicated. The prospects of improving visualization, developing new technologies and methods of minimally invasive surgery, as well as conducting clinical trials are discussed. In conclusion, the importance of a deeper understanding of the anatomy of the pelvic region and the development of new methods to improve the results of surgical interventions and reduce the risk of complications is emphasized